Continuity of home-based care for persons with dementia from formal and family caregivers' perspective. (April 2019) - Larsen, Lill Sverresdatter; Normann, Hans Ketil; Hamran, Torunn
Western health care policy emphasizes continuity of care for people with dementia. This paper presents formal and family caregivers' descriptions of collaboration in home-based dementia care and explores whether this collaboration inhibits or enables continuity of care and the use of the statutory individual plan. Empirical data were derived from 18 in-depth interviews with formal and family caregivers and brief fieldwork. The results reveal dynamic positions in collaborative practice and, from these positions, discrepancies in descriptions of practices and the needs of the person with dementia. Such micro-level discrepancies may serve as barriers for macro-level continuity of care objectives. To ensure continuity of care, formal and family caregivers must be aware of their positions and discuss specific expectations for information flow, involvement and care responsibilities. Individual plan can serve as a starting point for such discussions.